Doege-Potter syndrome: a rare presentation of a solitary fibrous tumor of the pleura - Estradioto, Liu; Araujo, Rodrigo Bettega de; Bergonse, Nelson, Neto; Araújo, Vanessa Bettega de; Coelho, Marlos de Souza; Silva, Larissa Luvison Gomes da (Brazilian Journal of Oncology, 2021)
Solitary fibrous tumors of the pleura usually have a benign behavior, although some may present malignant characteristics - recurrences, metastases, and paraneoplastic syndromes. When a solitary fibrous tumor is responsible for the development of hypoglycemia, we have a case of Doege-Potter syndrome. We describe a case of a male patient that presented recurring and severe hypoglycemia, being also diagnosed with an extensive intrathoracic mass, which was proven to be a solitary fibrous tumor of the pleura. The treatment, through the maintenance of proper serum levels of glucose (administration of solutions with glucose and steroids), followed by the surgical resection of the tumor, promoted the complete resolution of the hypoglycemia episodes. The early recognition of this condition and the proper treatment is essential for a good clinical outcome. It is important to underscore that the multidisciplinary evaluation (oncologists, radiologists, surgeons, and pathologists) of rare tumors is recommended to achieve better therapeutic results.
Keywords: Solitary fibrous tumor; Pleural; Paraneoplastic endocrine syndromes; Thoracic neoplasms.